A genome‐wide supported psychiatric risk variant in NCAN influences brain function and cognitive performance in healthy subjects. Issue 1 (13th September 2014) - Raum, Heidelore; Dietsche, Bruno; Nagels, Arne; Witt, Stephanie H.; Rietschel, Marcella; Kircher, Tilo; Krug, Axel
Abstract The A allele of the single nucleotide polymorphism (SNP) rs1064395 in the NCAN gene has recently been identified as a susceptibility factor for bipolar disorder and schizophrenia. NCAN encodes neurocan, a brain‐specific chondroitin sulfate proteoglycan that is thought to influence neuronal adhesion and migration. Several lines of research suggest an impact of NCAN on neurocognitive functioning. In the present study, we investigated the effects of rs1064395 genotype on neural processing and cognitive performance in healthy subjects. Brain activity was measured with functional magnetic resonance imaging (fMRI) during an overt semantic verbal fluency task in 110 healthy subjects who were genotyped for the NCAN SNP rs1064395. Participants additionally underwent comprehensive neuropsychological testing. Whole brain analyses revealed that NCAN risk status, defined as AA or AG genotype, was associated with a lack of task‐related deactivation in a large left lateral temporal cluster extending from the middle temporal gyrus to the temporal pole. Regarding neuropsychological measures, risk allele carriers demonstrated poorer immediate and delayed verbal memory performance when compared to subjects with GG genotype. Better verbal memory performance was significantly associated with greater deactivation of the left temporal cluster during the fMRI task in subjects with GG genotype. The current data demonstrate that common genetic variation in NCAN influences both neural processing and cognitive performance in healthy subjects. Our study provides new evidence for a specific genetic influence on human brain function. Hum Brain Mapp, 36:378–390, 2015. © 2014 Wiley Periodicals, Inc.